True grit American prints from 1900 to 1950 - Schrader, Stephanie; Glisson, James; Nemerov, Alexander (The J. Paul Getty Museum, 2019)
"An examination of thirty-eight prints by American artists from the first half of the twentieth century"--Provided by publisher.